Guidance on the structure and content of EFSA's scientific opinions and statements. (23rd September 2014) - ,
Abstract: The European Food Safety Authority (EFSA) asked the Scientific Committee to prepare a guidance document revising the structure and content of EFSA's scientific opinions and statements, to be implemented across EFSA's Scientific Committee and Panels. The new structure is proposed herein.